Early GalNAc O-Glycosylation: Pushing the Tumor Boundaries - Gomes, J (2017)
Glycosylation alterations are frequently observed in cancer cells and shape tumor progression. In this issue of Cancer Cell, Nguyen et al. show that GALNT1 relocation from Golgi to endoplasmic reticulum drives liver tumor growth and invasion, due to enhanced glycosylation and consequential activation of the extracellular matrix-degrading metalloproteinase MMP14. Glycosylation alterations are frequently observed in cancer cells and shape tumor progression. In this issue of Cancer Cell, Nguyen et al. show that GALNT1 relocation from Golgi to endoplasmic reticulum drives liver tumor growth and invasion, due to enhanced glycosylation and consequential activation of the extracellular matrix-degrading metalloproteinase MMP14.